Implementasi Corporate Social Responsibility (CSR) pada Hasnur Group (Study pada anak perusahan Hasnur Group Wilayah Kalimantan Selatan dan Kalimantan Tengah) - Hasnuryadi Sulaiman; Irwansyah Irwansyah; Maryono Maryono (Universitas Lambung Mangkurat, 2014)
CSR (Corporate Social Responsibility) is one of the obligations which have to be implemented by the company in accordance with the content of Article 74 of Company Limited Regulations (CLR), that is Regulations Number 40 Year 2007, through this Regulations, any industry or cooperatives are obliged to implement it. The increasing level of awareness on quality of life, social and environmental harmonization, is also influencing the activity in the business world. Therefore, the Constitution Provision on the role of company in the social responsibility was born. Here isone of the benefitsthatcan begleanedfrom thecompany'sCSRactivities. This is the context where the activity of Corporate Social Responsibility (CSR) has becoming the mandatory menu to the company, beyond the obligation which is outlined in The Regulations. The purpose of this thesis is to find out the application of Hasnur Group’s CSR on their subsidiaries which conduct the large-scale CSR in South and Central Kalimantan Region and to find out what are the obstacles faced and also propose solutions to the obstacles faced by the company in its implementation. Data in this thesis was analyzed qualitatively, that is secondary data in the theory form, its definition and substance from literature, Regulations Policy, and also primary data gained from interviews, field study and observation, which then being analyzed, in order to find the conclusion about the implementation of company social responsibility. Based on the analysis, it is concluded that in implementing their social responsibility, Hasnur Group has done some activities in Society Development, which are education, infrastructure, health improvement, socio-religious, and sports. While the obstacles found in the implementation of Hasnur Group’s CSR consist of internal and external constraints. Internal obstacle is caused by internal factors in the company itself, such as the policy inconsistency of work unit who supporting the program, the right person system has not been applied in the Bureau of Public Relation, less number of staffs, and the disharmony of turnover management elements with the policy. The external obstacles are the community participation is not optimal, the occurring of social problems, overlapping of community welfare activities, public’s high demand, and the low of public confidence and tribe’s work ethic. To overcome these obstacles through Solution Recommendation which is done to deal with the obstacles such us CSR training and community development, persuading the cooperation with NGO who have managerial capabilities, implementing an effective and efficient coordination, intensify internal coordination, strengthen the performance of duties and functions through intensive socialization and training, also holding regular meetings. Key Words : CSR (Corporate Social Responsibility)